THE RELATIONSHIP BETWEEN ARTIFICIAL INTELLIGENCE AND E-ACCOUNTING PROGRAMS: IMPACT ON THE QUALITY OF FINANCIAL REPORTS IN IRAQI BANKS - Асад Муншид Мохаммед; Асаад Ваххаб (Фінансово-кредитна діяльність: проблеми теорії та практики)
This study examines the correlation between electronic accounting software and artificial intelligence programs and their influence on the quality of financial reports in the banking sector of Iraq. The researchers devised a questionnaire comprising three dimensions to accomplish this objective. The initial set of questions pertained to using artificial intelligence applications by the study sample bank, either for customer service purposes or to achieve the bank's objectives. The second set of questions pertained to the accounting programs utilized, their advantages and disadvantages, and their compatibility with advancements in technology and communications. The third dimension encompassed inquiries on the essential attributes necessary for the excellence of financial statements by the criteria set by international financial reporting standards and the Central Bank of Iraq. Out of the 46 banks listed on the Iraq Stock Exchange in 2024, a sample of 31 institutions was chosen. Among them, there were 12 Islamic banks and 19 commercial banks. 217 questionnaires were distributed for analysis, with each bank receiving seven questionnaires for the directors of finance, internal audit, information systems, inspection, research and development, and their assistants to answer the research questions. The hypotheses were tested using IBM SPSS 29.0.10, employing practical analysis and simple and multiple linear regression. The research findings indicate that all banks in Iraq utilize electronic accounting. However, the quality of programs differs across banks based on the scale of financial activities and the amount of money they handle. The research also determined that artificial intelligence is advancing in the applications of banks, except for the Development Bank, the Bank of Baghdad, and the First Bank of Iraq. The study also demonstrates a strong correlation between the implementation of artificial intelligence in accounting and its positive impact on the reliability and accuracy of financial accounts.